Aqueous processing of organic semiconductors enabled by stable nanoparticles with built-in surfactants. Issue 14 (22nd March 2023) - Marcial-Hernandez, Raymundo; Giacalone, Sofia; Neal, William G.; Lee, Chang-Seuk; Gilhooly-Finn, Peter A.; Mastroianni, Giulia; Meli, Dilara; Wu, Ruiheng; Rivnay, Jonathan; Palma, Matteo; Nielsen, Christian B.
Abstract : Non-ionic polar side chains are leveraged in the molecular design of conjugated polymers to create stable surfactant-free polymer nanoparticle dispersions. An organic electronic device is prepared by processing the nanoparticles directly from water. Abstract : The introduction of oligoether side chains onto a polymer backbone can help to stabilise polymeric dispersions in water without the necessity of surfactants or additives when conjugated polymer nanoparticles are prepared. A series of poly(3-hexylthiophene) (P3HT) derivatives with different content of a polar thiophene derivative 3-((2-methoxyethoxy)methyl)thiophene was interrogated to find the effect of the polar chains on the stability of the formed nanoparticles, as well as their structural, optical, electrochemical, and electrical properties. Findings indicated that incorporation of 10–20 percent of the polar side chain led to particles that are stable over a period of 42 days, with constant particle size and polydispersity, however the particles from the polymer with 30 percent polar side chain showed aggregation effects. The polymer dispersions showed a stronger solid-like behaviour in water with decreasing polar side chain content, while thin film deposition from water was found to afford globular morphologies and crystallites with more isotropic orientation compared to conventional solution-processed films. As a proof-of-principle, field-effect transistors were fabricated directly from the aqueous dispersions demonstrating that polymers with hydrophilic moieties can be processed in water without the requirement of surfactants.